Spatial distributions of glutathione and its endogenous conjugates in normal bovine lens and a model of lens aging. (January 2017) - Nye-Wood, Mitchell G.; Spraggins, Jeffrey M.; Caprioli, Richard M.; Schey, Kevin L.; Donaldson, Paul J.; Grey, Angus C.
Abstract: Glutathione (GSH) is the archetypal antioxidant, and plays a central role in the protection of the ocular lens from cataract formation. High levels of GSH are maintained in the transparent lens, but with advancing age, GSH levels fall in the lens nucleus relative to outer cortical cells, thereby exposing the nucleus of the lens to the damaging effects of oxygen radicals, which ultimately leads to age-related nuclear (ARN) cataract. Under normal conditions, GSH also forms endogenous conjugates to detoxify the lens of reactive cellular metabolites and to maintain cell homeostasis. Due to the intrinsic gradient of lens fibre cell age, the lens contains distinct regions with different metabolic requirements for GSH. To investigate the impact of fibre cell and lens aging on the varied roles that GSH plays in the lens, we have utilised high mass resolution MALDI mass spectrometry profiling and imaging analysis of lens tissue sections. High Dynamic Range (HDR)-MALDI FTICR mass spectrometry was used as an initial screening method to detect regional differences in lens metabolites from normal bovine lenses and in those subjected to hyperbaric oxygen as a model of lens aging. Subsequent MALDI imaging analysis was used to spatially map GSH and its endogenous conjugates throughout all lenses. Accurate mass measurement by MALDI FTICR analysis and LC-MS/MS mass spectrometry of lens region homogenates were subsequently used to identify endogenous GSH conjugates. While the distribution and relative abundance of GSH-related metabolic intermediates involved in detoxification pathways remained relatively unchanged upon HBO treatment, those involved in its antioxidant function were altered under conditions of oxidative stress. For example, reduced glutathione levels were decreased in the lens cortex while oxidised glutathione levels were elevated in the lens outer cortex upon HBO treatment. Interestingly, cysteineglutathione disulfide, was detected in the inner cortex of the normal lens, but was greatly decreased in the HBO-treated lenses. These results contribute to our understanding of the multiple roles that GSH plays in maintenance of lens transparency and in the age-related metabolic changes that lead to lens cataract formation. Graphical abstract: Highlights: Bovine lens glutathione distribution is mapped using MALDI imaging mass spectrometry. Reduced glutathione is less concentrated following hyperbaric oxygen exposure. Multiple lens glutathione conjugate distributions are presented. Effects of lens hyperbaric oxygen exposure on glutathione conjugates are shown.